The effect of public sector efficiency on firm-level productivity growth The Italian case - Fadic, Milenko (OECD Economics Department Working Papers, 2019)
This paper investigates the causal effect of public administration efficiency on firm-level productivity. To this purpose, we combine newly available data from Italy on public administration efficiency of subnational governments with geo-localised firm-level data for the years 2004-2014. Italy provides a relevant setting to examine the relationship between public administration efficiency and firm productivity because of large and persistent spatial disparities in economic performance and local administrative capacity. The identification strategy exploits discontinuities that occur in local public-administration efficiency across provincial borders. The results suggest that local public administration efficiency has a large effect on firms' productivity growth. Increasing local public administration efficiency from the 25th percentile to the 75th percentile would raise the firm-level labour productivity in Italy by 2.4 percentage points